IDENTIFIKASI OKUPASI LAHAN PADA KAWASAN HUTAN LINDUNG PINANG LUAR KECAMATAN RASAU JAYA KABUPATEN KUBU RAYA - ratmo, Su; Said, Syafruddin; Oki W, Ganjar (Universitas Tanjungpura, 2013)
Pinang Luar Proteced Forest Location in Rasau Jaya subdistrict Kubu Raya regency West Borneo province immensity 1.177 hectare. The Methods to identify of Land Occupation are : 1) survey non terestrition cover map crop area interpretation citra landsat 7 ETM+ nda 2) Area observer method / groundcheck for seeing direct manner condition in field with data approach from interpretation landsat image 7 ETM+. Social data form pattern of occupation are collect also. From Citra Landsat interpretation, Pinang Luar Protected Forest immensity 1.170,44 hectare consist of 3 class : 1). Secondary swamp forest immensity 292,33 or 25%. 2) swamp thicket bushes immensity 466.11 hectare or 40%. 3) bushes mixed dry area agriculture immensity 422 hectareor 36%. The result of the research shows that, the landhave been occupied :(1) Shrubswamparea of ??466.11hectaresor 40%. Dryland farmingarea of?? 422 acres ofmixedbushor36% and residential areascovering 49.69hectaresor 4%. Keyword : Land Occupation, Protected Forest